COVERAGE OF SOYBEAN CROP BY SPRAYING LIQUID DUE NOZZLES AND SPRAYING VOLUME - ROMÁN, Rodrigo Alberto Alandia; CORTEZ, Jorge Wilson; FERREIRA, Marcelo da Costa; OLIVEIRA, José Rodolfo Guimarães di (Scientia Agraria, 2009)
The correct application of the crop protection products must provide a healthy agricultural production for the consumption, as well as preventing economic losses for the wastefulness, represented for the bad deposition of the product and consequence aggression to the environment. The goal of this research was to evaluate two tips of spraying nozzles (hollow cone nozzle and two flat fan nozzle annexed to a nozzle body DUO) and three spray volumes (100, 150 and 200 dm3 ha-1), whose application was for the control of the Asian soybean rust. An area of 288 m2 was used, with a randomized blocks design in a factorial 2x3 with 4 repetitions, total of 24 experimental parcels of 12 m2. For the spraying with hydraulical nozzles a costal spray of constant pressure kept by CO2 compressed with bar of 2 m was used. The analysis of the covering percentage was carried through by means of the use of hidro-sensible paper, that was placed in three position of the plant what it represents, in height, the third superior, average and inferior of the canopy. For both the third no interaction between the evaluated factors, was found and meither difference statistics between the spraying tips and the volumes. In absolute values the twin flat fan nozzle DUO presented minimum difference of covering in relation to the hollow cone nozzle, and for the spray volume of 200 dm3 ha-1 presented greater covering percentage.